INFLUENCE OF UNDERSTANDING INTEGRITY AND PROFESSIONAL VALUES FOR ACADEMIC ETHICS PRACTICES AMONG LECTURERS IN ISLAMIC RELIGIOUS HIGHER EDUCATION - Sufriadi Sufriadi; Mohd Zailani Mohd Yusoff (Universitas Ahmad Dahlan, 2020)
Education, the phenomenon of deterioration in academic ethics among lecturers, is alarming in Indonesia. That reflecting in decline in the value of integrity and the value of professionalism among lecturers. Therefore, this study focuses on the influence of understanding integrity and professional values on lecturers' academic ethics practices. The methodology of this study uses quantitative methods using descriptive survey studies. The data of this study were collected using questionnaire, where the understanding of integrity is measured with integrity according to the Hadith of the Prophet by Hanafi Hamdani (2014), professional values have measured using Wilson (2010) survey questionnaire on moral reasoning, and ethical decision making and academic ethics practices were measured using the College Teaching Behaviors Inventory (CTBI) developed by Braxton & Bayer (2003). The sampling method is to use a stratified sampling technique. Lecturers have randomly selected a total of 439 lecturers from five Universities of the Islamic Religious (PTKIN) in Aceh, Indonesia. Data were analyzed based on multiple regression. The findings showed that there was no significant effect of understanding of [p≥ .05 (.085)] and professional values [p≥ .05 (.140)] on lecturers' academic ethics practices. However, the findings of this study also show that a greater understanding of integrity contributes to the changing academic ethics of PTKIN lecturers than to professional values. This study implies that the aspect of understanding of integrity and professional value has enhanced through courses and training organized by the top management of PTKIN. The management of PTKIN should emphasize this aspect among the lecturers so that they can serve as role models for the younger generation.